Pojęcie supozycji sądu w poglądach polskich filozofów - Marek Panek (Studia Ecologiae et Bioethicae)
The concept of „supposition" has already been brought in by the scholastics (suppositio) for describing different relations between objects and names, which refer to these objects. In the XX century, the problem of supposition, understood som ew hat different than by the scholastics, was taken up by A. Meinong. His intention was taking notice of judgment existence, which does not express even the involvement of belief. Such a concept of supposition has been taken up and developed by many Polish philosophers (inter alia W. Witwicki, T. Czeżowski, K. Pasenkiewicz, K. Ajdukiewicz, H. Mehlberg, B. Gawęcki, and L. Kołakowski). They emphasized both subjective aspect - lack of belief moment, and objective aspect - non-verifiability.